Members of 3-O-Sulfotransferases (3-OST) Family: A Valuable Tool from Zebrafish to Humans for Understanding Herpes Simplex Virus Entry - Baldwin, John (Bentham Open, 2013)
The journey of many viruses to infect cells begins when the virus first binds to cell surface heparan sulfate (HS). The initial step of cell attachment or binding during herpes simplex virus type-1 (HSV-1) entry is mediated by envelope glycoprotein B (gB) and C (gC). The binding is followed by fusion between virus envelope and cell membrane during which HSV-1 glycoprotein D (gD) interacts with a modified form of HS know as 3-O-sulfated heparan sulfate (3-OS HS). The rare modification of 3-O-sulfation on HS chain is governed by enzymes known as 3-O-sulfotransferase (3-OST). Currently, there are seven isoforms of human 3-OSTs that have been identified, and with the exception of 3-OST-1, all other 3-OST isoforms allow HSV-1 entry and spread. Recently, the product of the zebrafish (ZF)-encoded 3-OST-3 was also recognized as a gD receptor, which mediates HSV-1 entry and cell-cell fusion similar to human 3-OST-3. Interestingly, the ZF system expresses multiple isoforms of 3-OST which could be very useful for studying the involvement of HS and 3-OS HS in virus tropism and virus-induced inflammation. In addition, therapeutic targeting of 3-OST generated HS is likely to bring about novel interventions against HSV-1. In this review we have taken a closer look at the potential of both human and ZF encoded 3-OSTs as valuable tools in HSV entry and inflammation studies.